The Mediating Role of Job Satisfaction in Influencing Intention to Stay - Nasywa, Adinda Dhiya; Prameka, Adelia Shabrina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to determine the effects of organizational culture and compensation on employees’ intention to stay, with job satisfaction serving as a mediating variable among PT Telkomsel employees. Design/Methodology/Approach – This study employs a quantitative explanatory research design. Using quota sampling, data were collected from 122 PT Telkomsel employees. The data were analyzed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) to examine both the direct and indirect relationships among the variables. Findings – The results indicate that organizational culture and compensation have significant positive effects on job satisfaction. However, neither organizational culture nor compensation has a significant direct effect on intention to stay. In contrast, job satisfaction has a significant positive effect on intention to stay and significantly mediates the relationships between organizational culture and intention to stay, as well as between compensation and intention to stay. Originality/Value This research provides value by analyzing the mediating role of job satisfaction in the relationships between organizational culture, compensation, and intention to stay, offering empirical insights that support more effective employee retention strategies.